Enhancing Students’ Geometric Reasoning through Rumah Gadang Ethnomathematics: A Local Instructional Theory Based on Realistic Numerical - Ainil Mardhiah; Armiati; Yerizon; I Made Arnawa (Jurnal Penelitian Pendidikan IPA, 2026)
This study developed a Local Instructional Theory (LIT) on geometric transformation based on Realistic Mathematics Education (RME) integrated with ethnomathematics of Rumah Gadang Minangkabau to enhance students' mathematical problem-solving ability. Using design research combining Plomp's development model and Gravemeijer and Cobb's framework, the research produced a Hypothetical Learning Trajectory, teacher's guide, and student workbook. Validation by experts showed very high validity scores: HLT (3.53), teacher's book (3.45), and student's book (3.49). Practicality testing revealed very practical ratings: teacher's book (92.50%) and student's book (83.97%). Effectiveness was demonstrated through post-test results, with 71.88% of students achieving mastery criteria and significant improvement across all problem-solving indicators. The findings indicate that integrating cultural contexts through ethnomathematics within an RME framework effectively supports students' conceptual understanding and problem-solving skills in geometric transformation. This LIT provides a culturally responsive instructional model that bridges abstract mathematical concepts with students' lived cultural experiences.